Biomarcadores inflamatorios y tiempo de enfermedad como predictores de apendicitis aguda complicada en pacientes menores de 18 años atendidos en el Hospital Regional de Loreto, 2023–2024 - Tulumba Avidon, Cristhian Luis (2025)
Objective: To determine the predictive capacity of disease duration (TE) and inflammatory biomarkers to identify complicated acute appendicitis (AAC) in patients under 18 years of age treated at the Regional Hospital of Loreto (HRL), 2023–2024. Methods: Observational, analytical, retrospective, and diagnostic accuracy study. A total of 114 patients with intraoperatively confirmed appendicitis were included. Cut-off points were obtained through ROC curves, and diagnostic performance was evaluated, along with a logistic regression model to assess combined predictive capacity. Results: AAC accounted for 63.2% of cases, and 60.5% were male. The most frequent intraoperative type was gangrenous appendicitis (29.8%); 41.2% of patients were aged 10–14 years, and 10.5% presented with fever. The mean age was 11.4 ± 3.6 years, and the mean hospital stay was 4.3 ± 3.8 days. Cut-off points and diagnostic performance: TE ≥ 47.5 h: AUC = 0.693; sensitivity 63.88%; specificity 71.43%; PPV 79.31%; NPV 53.57%; LR+ 2.24; LR− 0.51. NLR ≥ 6.807: AUC = 0.745; sensitivity 80.55%; specificity 61.90%; PPV 78.37%; NPV 65.00%; LR+ 2.11; LR− 0.31. PLR ≥ 270.17: AUC = 0.636; sensitivity 44.4%; specificity 80.95%; PPV 80.0%; NPV 45.94%; LR+ 2.33; LR− 0.68. MLR ≥ 0.65: AUC = 0.759; sensitivity 58.3%; specificity 85.7%; PPV 87.5%; NPV 54.5%; LR+ 4.08; LR− 0.49. In the final multivariate model (TE, NLR, MLR), good calibration was observed (Hosmer–Lemeshow p = 0.401), with an overall correct classification rate of 71.9% and AUC = 0.812. Conclusions: Individually, NLR showed the best overall performance as a screening test (sensitivity 80.55%), MLR had the highest confirmatory value (specificity 85.7%, LR+ 4.08), and PLR demonstrated complementary usefulness due to its higher specificity (80.95%). The combined model integrating TE, NLR, and MLR showed significant predictive capacity for the identification of complicated acute appendicitis (AAC) in the pediatric population. Their joint use constitutes a complementary, accessible, and low-cost clinical tool that can contribute to a more comprehensive assessment and better therapeutic decision making.